EFFECTS OF LOW TEMPERATURE STORAGE AND VAPOR HEAT TREATMENT ON THE QUALITY OF SWEET ORANGE - I. Hussain; A. Rab (Journal of Animal and Plant Sciences, 2015)
Oranges were treated with water vapor (50°C) for 0-20 minutes at 5 minutes interval and stored at 5°C for 75 days. Weight loss, Total Soluble Solids, surface pitting, TSS/Acid, disease incidence were increased, while reducing sugars, acidity and ascorbic acid were declined during storage. The highest weight loss (9.50%), Total Soluble Solids (11.10 ºBrix), surface pitting (16.40%), sugar acid ratio (7.63), disease incidence (10.53%) and the least acidity (1.41%) and ascorbic acid (29.21mg/100g) were recorded in storage for 75 days. Vapor heat treatment for 5 to 10 minutes resulted in least surface pitting (2.78%), TSS/Acid ratio (6.16), disease incidence (1.44%) and highest acidity (1.59%). But increasing VHT duration to 15-20 minutes resulted in highest weight loss (4.44%), Total Soluble Solids (10.57 ºBrix), TSS/Acid ratio (7.00) disease incidence (6.33%) and surface pitting (6.78%) as well as the least ascorbic acid content (35.76mg/100g). Vapor heat treatment (5-10 minutes at 50°C) can be utilized to maintain fruit quality for longer period and minimize chilling injury in cold storage. However, extended heat treatment beyond 10 minutes resulted in moisture loss and surface pitting similar to chilling induced pitting and hence adversely affected the fruit quality. in cardboard packages having two holes on each side for
Keywords: Vapor Heat Treatment; Sweet Orange; Storage; Low Temperature Storage.